2015
DOI: 10.1111/mec.13187
|View full text |Cite
|
Sign up to set email alerts
|

Concordance of bacterial communities of two tick species and blood of their shared rodent host

Abstract: High-throughput sequencing is revealing that most macro-organisms house diverse microbial communities. Of particular interest are disease vectors whose microbiome could potentially affect pathogen transmission and vector competence. We investigated bacterial community composition and diversity of the ticks Dermacentor variabilis (n = 68) and Ixodes scapularis (n = 15) and blood of their shared rodent host, Peromyscus leucopus (n = 45) to quantify bacterial diversity and concordance. The 16S rRNA gene was ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
107
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 123 publications
5
107
0
Order By: Relevance
“…This simple life history and feeding strategy provides an ideal system to investigate the natural drivers of microbiome diversity and its effect on pathogen transmission in a disease vector. A previous study did not find a correlation between host blood meal and Ixodes scapularis microbiomes (Rynkiewicz et al, 2015), yet Ixodes pacificus, the focal tick of this study, has a distinct natural history (Lane and Loye, 1989;Eisen et al, 2001). As a generalist, I. pacificus feeds on numerous vertebrate species that may be pathogen reservoirs, but the primary blood meal host for juvenile I. pacificus is the western fence lizard, Sceloporus occidentalis, a Borrelia-refractory host (Lane and Quistad, 1998;Kuo et al, 2000).…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…This simple life history and feeding strategy provides an ideal system to investigate the natural drivers of microbiome diversity and its effect on pathogen transmission in a disease vector. A previous study did not find a correlation between host blood meal and Ixodes scapularis microbiomes (Rynkiewicz et al, 2015), yet Ixodes pacificus, the focal tick of this study, has a distinct natural history (Lane and Loye, 1989;Eisen et al, 2001). As a generalist, I. pacificus feeds on numerous vertebrate species that may be pathogen reservoirs, but the primary blood meal host for juvenile I. pacificus is the western fence lizard, Sceloporus occidentalis, a Borrelia-refractory host (Lane and Quistad, 1998;Kuo et al, 2000).…”
mentioning
confidence: 49%
“…But it remains unclear what factors drive natural variation of the tick microbiome and whether such variation would affect pathogen transmission in the wild and therefore regulate disease risk. Prior field studies have identified microbiome differences by tick species (Hawlena et al, 2013), sex (Williams-Newkirk et al, 2014;Zhang et al, 2014) and region (Carpi et al, 2011;van Treuren et al, 2015) but have not found correlations with host blood or the immediate environment (Hawlena et al, 2013;Rynkiewicz et al, 2015).…”
mentioning
confidence: 99%
“…In addition, they carry numerous endosymbionts and commensals, which may provide nutrient supplements to the tick and also affect vector competence (reviewed in (Narasimhan & Fikrig, ; Bonnet et al., ; Clay & Fuqua, )). Studies have reported that the tick microbial community is variable depending on several factors such as source of host blood meal (Rynkiewicz, Hemmerich, Rusch, Fuqua, & Clay, ), feeding status (Menchaca et al., ; Swei & Kwan, ; Zhang et al., ), tick species, life stage, gender, and geographical origin (Carpi et al., ; Van Treuren et al., ; Williams‐Newkirk, Rowe, Mixson‐Hayden, & Dasch, ). However, very few studies have focused on the tick microbiome differences based on environmental conditions such as seasons of collection (Lalzar, Harrus, Mumcuoglu, & Gottlieb, ) or the immediate environment (Menchaca et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, vertical transmission of Bartonella spp. might be the explanation for presence of bacteria, if those larvae did not have an undetected blood meal [30]. Furthermore, B. henselae was detected in eggs from female ticks which were fed with infected blood but no Bartonella DNA was amplified from the larvae eclosed from those eggs [14].…”
Section: Discussionmentioning
confidence: 99%